Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure! Let's solve the given expression step by step. We want to find the square of the expression:
[tex]\[(0, 2x^2 + 5y^2 + 2)\][/tex]
We are specifically interested in squaring only the second part of the tuple:
[tex]\[2x^2 + 5y^2 + 2\][/tex]
Our goal is to compute:
[tex]\[\left(2x^2 + 5y^2 + 2\right)^2\][/tex]
To square the expression, we use the identity [tex]\((a + b + c)^2 = a^2 + b^2 + c^2 + 2ab + 2ac + 2bc\)[/tex]. Let's apply this step by step.
Here, [tex]\(a = 2x^2\)[/tex], [tex]\(b = 5y^2\)[/tex], and [tex]\(c = 2\)[/tex].
1. Square each term individually:
[tex]\[ (2x^2)^2 = 4x^4 \][/tex]
[tex]\[ (5y^2)^2 = 25y^4 \][/tex]
[tex]\[ 2^2 = 4 \][/tex]
2. Compute the cross-product terms:
[tex]\[ 2 \cdot (2x^2) \cdot (5y^2) = 20x^2y^2 \][/tex]
[tex]\[ 2 \cdot (2x^2) \cdot 2 = 8x^2 \][/tex]
[tex]\[ 2 \cdot (5y^2) \cdot 2 = 20y^2 \][/tex]
3. Combine all the terms:
[tex]\[ (2x^2 + 5y^2 + 2)^2 = 4x^4 + 25y^4 + 4 + 20x^2y^2 + 8x^2 + 20y^2 \][/tex]
Thus, the final squared expression is:
[tex]\[\left(2x^2 + 5y^2 + 2\right)^2\][/tex]
Simplified, it remains:
[tex]\[\left(2x^2 + 5y^2 + 2\right)^2\][/tex]
[tex]\[(0, 2x^2 + 5y^2 + 2)\][/tex]
We are specifically interested in squaring only the second part of the tuple:
[tex]\[2x^2 + 5y^2 + 2\][/tex]
Our goal is to compute:
[tex]\[\left(2x^2 + 5y^2 + 2\right)^2\][/tex]
To square the expression, we use the identity [tex]\((a + b + c)^2 = a^2 + b^2 + c^2 + 2ab + 2ac + 2bc\)[/tex]. Let's apply this step by step.
Here, [tex]\(a = 2x^2\)[/tex], [tex]\(b = 5y^2\)[/tex], and [tex]\(c = 2\)[/tex].
1. Square each term individually:
[tex]\[ (2x^2)^2 = 4x^4 \][/tex]
[tex]\[ (5y^2)^2 = 25y^4 \][/tex]
[tex]\[ 2^2 = 4 \][/tex]
2. Compute the cross-product terms:
[tex]\[ 2 \cdot (2x^2) \cdot (5y^2) = 20x^2y^2 \][/tex]
[tex]\[ 2 \cdot (2x^2) \cdot 2 = 8x^2 \][/tex]
[tex]\[ 2 \cdot (5y^2) \cdot 2 = 20y^2 \][/tex]
3. Combine all the terms:
[tex]\[ (2x^2 + 5y^2 + 2)^2 = 4x^4 + 25y^4 + 4 + 20x^2y^2 + 8x^2 + 20y^2 \][/tex]
Thus, the final squared expression is:
[tex]\[\left(2x^2 + 5y^2 + 2\right)^2\][/tex]
Simplified, it remains:
[tex]\[\left(2x^2 + 5y^2 + 2\right)^2\][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.